PROFIL SURJA HUBUNG KARENA PROSES ENERGIZED PADA SALURAN TRANSMISI 500 KV - - Yuniarto (PSTE UNIMUS, 2014)
Transient over voltage that happened because switching surge have to be paid attention to don't cause the damage equipments of insulation coordination system. This research aim to perceive the transient over voltage at the end of 500 kv transmission line caused energized process by using EMTP (Electromagnetic Transients Program) as toll to simulate the energized process. Data for this research was taken from 500 kv transmission line Ungaran-Pedan. From this research was expected can become a reference for power company in planning insulation coordination at transmission line. Result of research show that transient over voltage at the end of 500 kv transmission line caused energized process reach more or less twice its nominal voltage Keywords : energized, karateristik, transient over voltage, EMTP